Cirrhosis, von Willebrand Factor (vWF) and the low incidence of metastatic malignancy in injured liver - Alonso, Daniel Fernando (2015)
The work by Yilmaz et al. in The Eurasian Journal of Medicine provides clinical evidence for the correlation between increased levels of von Willebrand factor (vWF) and the stage of cirrhosis. The authors observed significantly higher vWF antigen levels in cirrhotic patients compared to a control group, and also an increase with the increasing stages of cirrhosis according to the Child-Pugh score. These results indicate that vWF is produced as a reliable marker of endothelial dysfunction during hepatocellular failure in cirrhosis. Besides, in light of the results of Yilmaz et al. [1] another perspective regarding the low incidence of metastatic malignancy in cirrhotic patients and the potential role of vWF should be pointed out. The blood coagulation protein vWF is mainly secreted by endothelial cells into the subendothelial space and into the plasma, serving as an adhesive link between platelets and the vascular wall. It is known that liver sinusoidal endothelial cells are a prominent source of vWF, not only during haemostatic processes but also in tissue injury. Interestingly, many studies have implicated vWF as a key factor in resistance to metastasis. Terraube et al. demonstrated that vWF plays a protective role against metastatic spread in a vWF-deficient mouse model. It appears that vWF can induce apoptosis of metastatic cells early after their arrest in the vasculature of the target organ. In the same line, Mochizuki et al. found that aggressive cancer cells producing high levels of metalloproteinase ADAM28 are able to avoid vWF-induced apoptosis at micrometastatic sites. ADAM28 binds and degrades vWF, thus favouring the survival of metastatic cells in the target organ.